PENGARUH PASSION TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR DIMEDIASI OLEH ORGANIZATIONAL COMMITMENT PADA GURU SMA NEGERI 5 KOTA BANDA ACEH - Mulyadi, Andy; Suryani, Ade Irma (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2019)
Abstract: This sudy aims to measure the influence of passion on organizational citizenship behavior at teachers of SMA Negeri 5 Banda Aceh with organizational commitment as mediating variable. Sampling method in this sudy using saturation sampling with 57 respondents. The result showed that obsessive passion was unrelated to organizational citizenship behavior, while harmonious passion to organizational citizenship behavior has positively and significantly. Obsessive passion was unrelated to affective commitment, while harmonious passion has a significant positive relationship on affective commitment. Affective commitment has significent positive relationship on organizational citizenship behavior. Affective commitment doesn’t mediate the relationship between obsessive passion on organizational citizenship behavior. Affective commitment mediated partially the relationship between harmonious passion and organizational citizenship behavior.